Verificação de contorno de grão serrilhado via precipitação descontínua e avaliação da sua influência na resistência a fluência em liga NI-CO-AL - Martins, João Marcos Ribeiro (Universidade Federal Rural do Semi-Árido, 2017)
Ternary alloys of nickel, cobalt and aluminum have been studied in applications of technological relevance, such as ferromagnetic materials with shape memory effect and generation of nanostructures through discontinuous precipitation process. The discontinuous precipitation of the 􀈖 ' phase in Ni-Co-Al alloys can move the contour of the grain and, when dissolved, leave a serrated shape. The serrated grain boundary influences the mechanical properties of the material and can increase its resistance to creep. Samples of Ni-37-12 in atomic composition were produced, some with normal grain outline and others submitted to the formation of contour of serrated grain through discontinuous precipitation. The samples of both types were submitted to creep tests, in order to compare deformation values for the same temperature and pressure conditions and the same time intervals. The creep tests were performed at high temperatures and under compression. The temperature and pressure were parameters that affected the results obtained for this mechanical property. Tests carried out at a temperature of 750 ° C at a pressure of 150 MPa confirmed the hypothesis that the serrated grain boundary shape may increase the creep resistance of the material, while the tests performed at a temperature of 800 ° C with a pressure of 100 MPa revealed a little conclusive result for short time intervals and, for longer intervals, contradicted the hypothesis, confirming the influence of temperature and pressure parameters on the results obtained.
Monografia
Keywords: Precipitação descontínua; Contorno de grão serrilhado; Fluência; Discontinuous precipitation; Serrated grain boundary; Creep; ENGENHARIAS::ENGENHARIA MECANICA